EFEKTIVITAS EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS MASALAH (PBL) BERBANTUAN MEDIA MULTIREPRESENTASI TERHADAP PEMAHAMAN SISWA TENTANG KONSEP SUHU DAN PERUBAHAN FASA - Farhan, Farid Maulana; Yuberti, Yuberti; Anggraini, Welly (EduFisika: Jurnal Pendidikan Fisika, 2025)
This study aims to examine the effectiveness of Problem-Based Learning (PBL) supported by multirepresentation media in improving students' conceptual understanding of temperature and changes in the state of matter. A quantitative approach with a quasi-experimental pretest–posttest design with non-equivalent control groups was used. The research participants consisted of two classes of 11th-grade students majoring in science at SMA Negeri 1 Tumijajar, selected through cluster sampling. Data were collected through a test that measured seven indicators of conceptual understanding. The results showed a significant increase in conceptual understanding in both groups; however, the experimental group achieved much higher posttest scores and levels of improvement. The experimental group obtained an average N-gain of 0.68, while the control group achieved 0.49. Inferential analysis confirmed a significant difference in posttest scores between the groups, demonstrating the effectiveness of PBL supported by multirepresentational media in facilitating conceptual understanding. The improvement was particularly evident in higher-order indicators such as interpreting, comparing, explaining, and concluding. These findings suggest that the integration of multi-representation media in PBL is very effective as a cognitive scaffold to enhances students' ability to construct and translate abstract physics concepts, making learning more effective, meaningful, and cognitively structured.